Sustainability Reporting in Indonesian Oil and Gas Companies: Formalities or Awareness? - Rahmah, Amelia; Wardani, Devy Ayu Kusuma; Tyas, Putri Salindri Ayuning; Wijayani, Dahyang Ika Leni (Owner : Riset dan Jurnal Akuntansi, 2024)
The implementation of the Sustainable Development Goals (SDGs) which was inisiated at the meeting in New York, September 2015 has become the focus of the Indonesian to achieve global development targets. There are 17 goals in the SDGs and are presented through a sustainability report, especially for oil and gas sector companies in Indonesia. The purpose of this study was to analyze all oil and gas sector companies listed on the Indonesia Stock Exchange and to find out the role of vocational college students in preparing SDGs. The research used qualitative methods in the form of a literature review by reading sources related to research and studying texts by analyzing sustainability reports from oil and gas sector. From this research, it is known that not all companies comply with the making of sustainability reports and it is still felt to be less than just a formality. Companies are expected to continue to review the sustainability report thoroughly and continuously so that it can be used as a force in determining the direction of the company's strategy towards goals related to the SDGs. The role of vocational college students is very important in making sustainability reports to support the SDGs, in which students are responsible for the tridharma of higher education and agents of change.